Geomorphological Analysis of Tectonic Activity in the Eastern Maysan Governorate (International Journal of Environmental Sciences, 2025)
This study examines the geomorphological analysis of tectonic activity in the eastern part of Maysan Governorate, with a focus on structural features such as faults, fractures, folds, and their geographical distribution. The research is based on an analysis of the geological history of the region, which reveals that it has undergone two major phases of tectonic movement:The first phase (older): Associated with the movement of the Arabian and Iranian plates, beginning in the Permian and continuing through the Neogene period. This phase contributed to the formation of a passive margin of an extensional basin.The second phase: Influenced by inherited basement faults during the Cretaceous and Eocene periods, which increased tectonic activity rates.Remote sensing data from LANDSAT 8 were utilized to analyse structural lineaments through the application of spectral and spatial digital processing techniques. The results indicated that the near-infrared band (Band 4) and mid-infrared bands (Bands 5 and 7) were most effective in detecting geological features. The study also revealed the significant role of faults in shaping morphotectonic features, such as changes in bedding dip, fold deflections, drainage pattern reversals, and modifications in alluvial fan morphology, indicating recent tectonic activity.